Avaliação de resistência de cultivares de cana-de-açúcar ao Sugarcane yellow leaf virus (SCYLV) e ao seu afídeo vetor Melanaphis sacchari - Rodrigues, Mariana Pelegrini [UNESP] (2015)
This research focused on the evaluation of resistance in sugarcane (Saccharum spp.) to the Sugarcane yellow leaf virus (SCYLV) and to its main vector, the sugarcane aphid Melanaphis sacchari (Zehntner). Five sugarcane varieties (IACSP93 3046, IACSP95 5000, IACSP95 5094, IACSP96 3076, and SP71 6163), chosen due to their economic importance to Brazilian sugarcane growing areas, were multiplied by tissue tip culture, indexed, and evaluated in terms of the aphids' behavior by the traditional antibiosis, antixenosis and EPG (Electrical Penetration Graphs). At the same time, a second test was set up for evaluating the development of yellowing leaf on field after inoculation with SCYLV. The aphid showed preference for IACSP96 3076 and higher population growths indexes on IACSP95 5000. We found out favorable parameters on the insect behavior over variety SP71 6163 that reinforce its previously known high susceptibility to SCYLV infection. We also demonstrate by these experiments the existence of pre and post-phloematic penetration factors that influence the behavior of M. sacchari and further transmission of SCYLV, and proving through initial assessments of symptoms severity that YLS yellowing of sugarcane expressed faster and more strongly in this cultivar